STUDI KASUS: PEMENUHAN KEBUTUHAN AKTIVITAS TERHADAP IBU SECTIO CAESAREA DI RUMAH SAKIT TK II PUTRI HIJAU - Broyendin, Broyendin; Evamona, Evamona; Suharto, Suharto (SENTRI: Jurnal Riset Ilmiah, 2023)
Sectio Caesarea is an artificial childbirth in which the fetus is born trought the incision of front wall of stomach and the womb wall on condition that the womb is complete and the fetus weight is not less than 500 gram. Anesthesia is used in the operation process so that patient does not feel painfull in the surgery because the pain will cause the women in the post- caesarea to get difficulty in her daily activities which contitute her basic needs. The activities, include standing, walking, working, eating,drinking etc. When the body is healthy, respiratory system and body circulation will funcition well and body metabolism will function optimaly Method the research instrument is observation shetts and interview shetts is patients at Tk II Putri Hijau Hospital, Medan. Results In the case I the patient cannot move in the post -operation, and in the activity level3 , he is able to move by minimal aid, while in the case II , the patient encounters difficulties to move and in the activity level 2, he was able to move with aid of auxiliary apparatus. The need for physical activity is aided by early mobilization Conclusion it is concluded that the need for physical activity can be done idenpedently . Nurses should involve patients and their families in every action in order to train patients in doing their